2014
DOI: 10.1002/mma.2828
|View full text |Cite
|
Sign up to set email alerts
|

3‐D spatio–temporal structures of biofilms in a water channel

Abstract: We develop a numerical predictive tool for multiphase fluid mixtures consisting of biofilms grown in a viscous fluid matrix by implementing a second-order finite difference discretization of the multiphase biofilm model developed recently on a general purpose graphic processing unit. With this numerical tool, we study a 3-D biomass-flow interaction resulting in biomass growth, structure formation, deformation, and detachment phenomena in biofilms grown in a water channel in quiescent state and subject to a she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…However, if the biofilm grows in a moving fluid the structural properties of the biofilm will differ [ 41 ]. Experimental work has shown that high shear forces result in thinner, denser, stronger and filamentous biofilms while low shear forces result in biofilms with mushroom and circular shapes [ 42 ]. It is also reported in the literature that biofilms produce undulating shapes when grown in flow fields [ 23 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, if the biofilm grows in a moving fluid the structural properties of the biofilm will differ [ 41 ]. Experimental work has shown that high shear forces result in thinner, denser, stronger and filamentous biofilms while low shear forces result in biofilms with mushroom and circular shapes [ 42 ]. It is also reported in the literature that biofilms produce undulating shapes when grown in flow fields [ 23 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Current velocity affected the architecture and dynamics of natural, multiphyla, and cross-trophic level biofilms from a forested piedmont stream 15 . Recently, a 3-D biofilm model was used to illustrate the effects of water flow on biofilms in a water channel and found that excessive shear force could detach or bend the thin-necked biofilm colony (a common structure during biofilm formation), decreasing the biofilm thickness and roughness 36 . The heterogeneity of biofilms was also affected by surface characteristics of plant leaves.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the flux amplitudes β j (see (17)), the exchange flux functions e jk (v(x)) = e k (v(x)), k = 1, 2, 3 (see (12)), are given by the components e k (v) = −v • i k of v corresponding to exchange reactions, where i k is a 6-vector with a 1 in the kth place and 0's elsewhere. In this example,…”
Section: 2mentioning
confidence: 99%
“…where r jk is a consumption/production rate (units of time −1 ) and Y jk is a yield coefficient (units of volume fraction per concentration) [38]. On larger scales, advective transport in a bulk flow may also be of importance and can be included [12,14,22,23,28,51,66] but will not be considered here for simplicity. C is the vector with components of all dissolved concentrations C k exterior to cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation